Vulnerability assessment on UiTM student ID card / Muhamad Hazha Hashim - Hashim, Muhamad Hazha (2014)
The Mifare Classic is the most widely used contactless smart card in the world. Its communication protocol is based on the open ISO-14443-A standard, but the authentication and encryption protocols are proprietary. Several researchers have cracked its encryption and proposed attacks to recover the access keys. This paper will examine the MIFARE Classic 1K contactless card that being used as the student ID card in University Technology MARA (UiTM). In doing so, we have identified its major weakness and have recommended ways to mitigate it.